Errors Associated With Excess Air Multipoint Measurement Systems - Ramsunkar Charlene; van Tonder Chris; Schmitz Walter (Chemical and Process Engineering)
Boiler combustion air is generally controlled by the excess air content measured at the boiler economiser outlet using oxygen (O2) analysers. Due to duct geometry and dimensions, areas of high and low O2 concentrations in the flue gas duct occur, which poses a problem in obtaining a representative measurement of O2 in the flue gas stream. Multipoint systems as opposed to single point systems are more favourable to achieve representative readings. However, ash blockages and air leakages influence the accuracy of O2 measurement. The design of multipoint system varies across ESKOMs’ Power Stations. This research was aimed at evaluating the accuracy of the multipoint oxygen measurement system installed at Power Station A and to determine the systematic errors associated with different multipoint systems designs installed at Power Stations' A and B. Using flow simulation software, FloEFDTM and Flownex®, studies were conducted on two types of multipoint system designs This study established that significantly large errors, as high as 50%, were noted between the actual and measured flue gas O2. The design of the multipoint system extraction pipes also introduces significant errors, as high as 23%, in the O2 measured. The results indicated that the sampling errors introduced with Power Station A’s system can be significantly reduced by adopting the sampling pipe design installed at Power Station B.